Radial glia and radial glia-like cells: Their role in neurogenesis and regeneration - Miranda-Negrón, Yamil; García-Arrarás, José E. (Frontiers in Neuroscience, 2022)
Radial glia is a cell type traditionally associated with the developing nervous system, particularly with the formation of cortical layers in the mammalian brain. Nonetheless, some of these cells, or closely related types, called radial glia-like cells are found in adult central nervous system structures, functioning as neurogenic progenitors in normal homeostatic maintenance and in response to injury. The heterogeneity of radial glia-like cells is nowadays being probed with molecular tools, primarily by the expression of specific genes that define cell types. Similar markers have identified radial glia-like cells in the nervous system of non-vertebrate organisms. In this review, we focus on adult radial glia-like cells in neurogenic processes during homeostasis and in response to injury. We highlight our results using a non-vertebrate model system, the echinoderm Holothuria glaberrima where we have described a radial glia-like cell that plays a prominent role in the regeneration of the holothurian central nervous system.